The infinite adventures of Supernova. 1, Pepper Page saves the universe - Walker, Landry Q. (Landry Quinn) (First Second, 2021)
In the future, fifteen-year-old orphan Pepper Page hides from the peer pressure and bullying in her high school by immersing herself in the classic comic book adventures of her heroine, Supernova. When Pepper encounters a strange cat named Mister McKittens, an evil science teacher named Professor Killian, and a science experiment gone wrong, she is forced out of hiding to come to terms with her past and her future.